2000
DOI: 10.1002/(sici)1097-4628(20000628)76:14<2026::aid-app5>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Poly(dimethylsiloxane)/poly(hexamethylene oxide) mixed macrodiol based polyurethane elastomers. I. Synthesis and properties

Abstract: ABSTRACT:The compatibilizing effect of poly(hexamethylene oxide) (PHMO) on the synthesis of polyurethanes based on ␣,-bis(6-hydroxyethoxypropyl) poly(dimethylsiloxane) (PDMS) was investigated. The hard segments of the polyurethanes were based on 4,4Ј-methylenediphenyl diisocyanate (MDI) and 1,4-butanediol. The effects of the PDMS/ PHMO composition, method of polyurethane synthesis, hard segment weight percentage, catalyst, and molecular weight of the PDMS on polyurethane synthesis, properties, and morphology w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
113
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 114 publications
(116 citation statements)
references
References 22 publications
3
113
0
Order By: Relevance
“…The PU co-polymers were synthesized from 4,4 0 -methylene di(p-phenyl isocyanate) (MDI) and 1,4-butanediol (BDO) for the hard segments via a two-step condensation process as reported elsewhere [23,24]. Each co-polymer contained 40 wt.% hard segments.…”
Section: Polyurethane Co-polymersmentioning
confidence: 99%
“…The PU co-polymers were synthesized from 4,4 0 -methylene di(p-phenyl isocyanate) (MDI) and 1,4-butanediol (BDO) for the hard segments via a two-step condensation process as reported elsewhere [23,24]. Each co-polymer contained 40 wt.% hard segments.…”
Section: Polyurethane Co-polymersmentioning
confidence: 99%
“…Polyurethane has some specificity with respect to its film forming ability, good toughness, high abrasion resistance, good chemical resistance, excellent adhesion, high tear strength, tunable mechanical strength, adequate flexibility and elasticity, including fabrication versatility due to the versatility in structure and composition of the components [1][2][3]. Polyurethanes are generally segmented block copolymers having alternating soft and hard segments.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the large difference in polarity between the urethane/urea hard segments and the siloxane soft segments, there are now two general approaches to the synthesis of PUS and PUUS copolymers. The first involves the presence of polyether or polyester segments as co-soft segments, in order to improve the miscibility of PDMS with the urethane or/and urea units [83][84][85]. Gunatillake et al [86,87] reported that thermoplastic PUs based on mixed PDMS and poly(hexamethylene oxide) (PHMO) as the soft segments exhibit excellent tensile strength (~ 28 MPa), elongation at break (~ 580 %) and Young's modulus (~ 33 MPa).…”
Section: Poly(dimethylsiloxane)-based Biopusmentioning
confidence: 99%